Pertanggungjawaban Lembaga Perkreditan Desa (LPD) Desa Adat Ungasan Atas Ketidakmampuannya dalam Memenuhi Hak Nasabah Pemegang Simpanan - I Gede Surya Pratama Putra; I Nyoman Sukandia; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2021)
LPD is an economic institution belonging to the Traditional Village. LPD is formed, managed by Desa Pakraman, and serves financial transactions only within the internal environment of Desa Pakraman. LPD administrators are elected, stipulated, legalized, and dismissed by means of the village paruman. From all levels the LPD management comes from indigenous peoples and cannot avoid problems that arise in the institution, thus, this research focuses on to manage loans (credit) to customers so as to avoid bad credit at the Village Credit Institution (LPD) Adat Ungasan and to examine the responsibility of the Ungasan Traditional Village Credit Institution (LPD) in fulfilling the rights of customers who hold deposits. The research method used in this research is empirical research method. Based on the research results, it can be concluded that there are four parts to the procedure for giving credit to the LPD, namely: The Credit Section, the Head of the LPD, the Cashier Section and the Bookkeeping Section. Furthermore, all losses of the Ungasan Traditional Village LPD shall be borne by the Traditional Village, in the event that the Traditional Village is able to back up the losses of the Ungasan Customary LPD, provided that the old Ungasan LPD administrators cover all losses to the Traditional Village because the Traditional Village is a communal customary organization or promoting togetherness